Correction to: Facilitating the implementation of clinical technology in healthcare: what role does a national agency play? - Gill Harvey; Sue Llewellyn; Gregory Maniatopoulos; Alan Boyd; Rob Procter (BMC, 2018)
Upon publication of the original article [1], Gregory Maniatopoulos' name was incorrectly given as 'Greg Maniatopoulous'. This has now been corrected in the original article.